Alternatif Model Kepemimpinan pada Era Globalisasi - Nida Hasanati (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
The current global situation is characterized by a variety of leadership requires a paradigm change in accordance with change itself. Leaders who have superior characteristics and exhibit adaptive behaviors to change, leaders are able to capture the phenomenon in the leadership and understand who the followers, so the process of directing, guiding, motivating and preparing future leaders can be achieved with good. This paper intends to provide an overview of the changes in the present paradigm, trying to see the similarities between transformational leadership as the present leadership with recognized leadership rooted in Indonesian society and initiated by Ki Hajar Dewantara. In addition it also presented about followership , which actually integrates with the leadership itself, thus the possibility of achieving success in the lead is not a difficult thing.